On the constant in the nonuniform version of the Berry-Esseen theorem - K. Neammanee (International Journal of Mathematics and Mathematical Sciences)
In 2001, Chen and Shao gave the nonuniform estimation of the rate of convergence in Berry-Esseen theorem for independent random variables via Stein-Chen-Shao method. The aim of this paper is to obtain a constant in Chen-Shao theorem, where the random variables are not necessarily identically distributed and the existence of their third moments are not assumed. The bound is given in terms of truncated moments and the constant obtained is 21.44 for most values. We use a technique called Stein's method, in particular the Chen-Shao concentration inequality.